Karakter Antomi Daun Tumbuhan Mangrove Akibat Pencemaran di Hutan Mangrove Kabupaten Cilacap - Siti Samiyarsih; Tata Brata Suparjana; Juwarno Juwarno (Fakultas Biologi | Universitas Jenderal Soedirman, 2016)
This research was aimed to observe the anatomical character of mangrove plants leave and examine the differences from leaves anatomical character of mangroves in Donan river and Tritih forest in Cilacap regency as an self-adaptation indicator. The method which is used was survey method by collecting leaves sample of each mangrove plants. The sample was preparated using embedding method, and stained with safranin 1% disolved in alcohol 70%. The parameter of variable which is observed in leaves anatomical character are thickness of leaves, leaves mesophyll thickness, cuticle thickness, stomata length size, and amount of stomata and trichome per leaves unit area. The data were analyzed with t-test for examining anatomical character difference. The results showed that four usual types of mangrove plants such as Achantus ilicifolius, Rhizospora mucronata, Aegiceros corniculatum, and Bruguiera gymnorrhiza have similar leaves anatomical structure. The anatomical character from polluted habitat were different from unpolluted habitat. This differences was showed in leaves mesophyll thickness, cuticle thickness, stomata length size, and amount of stomata and trichome per mm2 leaves unit area.